Análise do desenvolvimento sustentável na Mesorregião Oeste do Paraná: uma aplicação do barômetro da sustentabilidade - Hachmann, Flavia (2015)
Due to the degrading effects to the environment, resulting from the economic growth and from the high consumption standards, discussions about Sustainable Development have been fostered, which have been widely discussed in recent decades by mankind in order to ensure the quality of life of this and future generations through proper management of natural resources. Therefore, it becomes important to identify indicators to measure progress toward Sustainable Development perspective, able to provide a solid basis for decision in the various spheres of society, contributing to the creation of conditions conducive to sustainability. Therefore, the research aimed to analyze the Sustainable Development of Mesoregion West of Paraná in comparison with the rest of the state, for the years 2000 and 2010, evaluating the Welfare of the Human System and the Welfare of the Environmental System the region, through a data collection and use of the Barometer of Sustainability tool. The research method was quantitative and qualitative, to the extent that techniques for analysis, decomposition, aggregation and discussion of data were employed, stages according to composition the Barometer of Sustainability. Moreover, in its methodological aspects, the research has an exploratory and documentary feature. The results showed that the Mesoregion West of Paraná ranked in 2000 as Nearly Untenable and in 2010 as Untenable.